Bacterial Meningitis Epidemiology and Vaccination - Stuart, James M. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This timely collection of expert papers draws attention to the global burden of meningitis and the challenges faced by the WHO's roadmap to defeat meningitis by 2030. The three main goals of the meningitis roadmap are to eliminate epidemics of bacterial meningitis, reduce cases and deaths from vaccine-preventable bacterial meningitis, and reduce disability and improve quality of life after meningitis of any cause. This book includes a wide range of original research and reviews on epidemiology and vaccination of bacterial meningitis that have direct relevance to advancing the goals of the roadmap.